REPRESENTASI NILAI-NILAI BUDAYA JAWA DALAMâ€ NOVEL BIOLA TAK BERDAWAIâ€ KARYA SENO GUMIRA ADJIDARMA ( Sebuah Kajian Antropologi ) - Pangripty Nanda Sukmana, Chitra (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2019)
The title of this research is Java Culture Values in Biola Tak Berdawai Novel ( Antropology Discussion ). And start from the principle that literature is kind of social reality in societies group as potential which describes, idea, message and certain value. The data which is submitted un the words or pictures, It is not numeral,or drawing the datas which be analyzed by Biola Tak Berdawai novel. The main purpose is descriptive describing, or drawing the datas which be analyzed by Biola Tak Berdawai novel. From this result can be explained that in Biola Tak Berdawai novel there are Culture of character include of religion emotion and believe of ghaib shape, dead Life and the power of God, the relation of human with them as harmonious attitude, respect, make an help, the relation human with time which basic in the past event and it will become to change in the future